Embedding Interventions to Promote Self-Determination within Multitiered Systems of Supports. Issue 4 (1st October 2016) - Shogren, Karrie A.; Wehmeyer, Michael L.; Lane, Kathleen L.
ABSTRACT: Schools are increasingly exploring the implementation of multitiered systems of support. This article reviews the literature pertaining to efforts to promote self-determination to provide initial direction as to how interventions and supports to promote self-determination could be implemented within a tiered framework. The intent is to provide direction to the field on how such an approach can engage all students—including students with and without disabilities—in their learning across the lifespan to promote positive school and postschool outcomes. Specifically, we review interventions and supports that have been described in the literature pertaining to self-determination, organizing our review and analysis around the traditional three-tier approach. Implications for future research and development to promote the universal applicability of self-determination are discussed.